Kajian Filsafat Ontologi Martin Heidegger atas Peran Musik dan Nyanyian Liturgi bagi Perkembangan Hidup Umat Beriman - Crysan Dwiputra Malla; Robert Pius Manik (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
This article deals with the ontological philosophy of Martin Heidegger in the context of discovering the meaning of liturgical symbols, specifically one of liturgical music and chant in the Catholic Church. The aim of this study is to explain the symbolic meaning of liturgical music and chant and to reflect on its relevance in enriching the liturgical capacity of the faithful. The paper is intended as a literature review. The author reviews Louis-Marie Chauvet's book, Symbol and Sacrament, as well as other works about Heidegger's philosophy, such as the writings of Armada Riyanto. This study finds that liturgical symbols, such as music and chants performed in the liturgy, are not merely entertainment to please the eyes and ears of the people. These are symbols that transmit the content and the message of faith. The performance of liturgical symbols can help people understand and experience the strength and beauty of liturgical celebrations.